Peranan Keuangan Berkelanjutan Pada Bank BUMN Dalam Mendukung Sustainable Development Goals: The Role of Sustainable Finance in State-Owned Banks in Supporting the Sustainable Development Goals - Saraswati, Wiwik (MEDIA RISET EKONOMI [MR.EKO], 2025)
Banks are required by the government to make a sustainability report in 2020 so that economic growth is expected to increase and avoid the emergence of negative impacts caused by the economic development process. This encourages the bank to pay attention to environmental impacts that prioritize the harmony of economic, environmental and social aspects. OJK's Sustainable Finance Roadmap Phase II (2021-2025) for the banking sector is a continuation of the Roadmap Phase I (2015-2019). The goal is to accelerate the establishment of a comprehensive sustainable finance ecosystem in Indonesia. For banking, this roadmap focuses on integrating environmental, social, and governance (ESG) aspects into all operations, from internal policies, products, to services. This is needed to contribute to Indonesia's economic development efforts and contribute directly to the achievement of the Sustainable Development Goals (SDGs). The analysis method used is qualitative descriptive. Based on the road map that has been made by the OJK, banks in Indonesia have committed to the Sustainable Financial Action Plan (RAKB) to provide credit to creditors who have certification in accordance with Environmental, Social and Governance (ESG) principles and AMDAL (Environmental Impact Analysis) permits in the green construction, agriculture, green infrastructure, forestry, renewable energy, recycling industry and energy efficiency sectors